An Investigation of Family Therapy-Based Training on an Adolescent’s Self-Harm and Character Strengths - Barati Sedeh, Maryam; Molalo, Laya; Korang Beheshti , Fereshte; Jafarzadeh Khademlou, Roya; Rayati Rad , Ashraf (Shahroud Journal of Medical Sciences, 2023)
Background: The prevalence of non-suicidal self-injury has increased in adolescents. This study aimed to assess the effectiveness of family therapy compared with treatment as usual in improving character strengths and reducing self-harm repetition in adolescents. Methods: The research was designed as semi-experimental with a pre-test, post-test, and control group. The statistical population was all students of Tehran's middle schools with self-injury from October to September 2022. 53 eligible adolescents were selected purposefully. The participants were randomly divided into two groups: a family therapy counseling (n=27 people) and a control group (n=26 people). The experimental group received sixteen 75-min counseling sessions held weekly, while the control group underwent no interventions. Both groups received post-test evaluations following these sessions. Then, the Deliberate Self-Harm Inventory and Values in Action Inventory of Strengths scale (VIA-Youth) pre- and post-intervention were implemented. SPSS 24 used a multivariate analysis of the covariance (MANCOVA) version. Results: The effect of family therapy on the self-injury variable was significant (F=32.61; Pvalue<0.001). Also, the effect of family therapy on character strengths (F=24.81; Pvalue<0.001) was confirmed. In addition, it related the largest effect size to the self-injury variable (0.648), which shows that 64% of the total variances of the experimental and control groups result from a family therapy approach. Conclusions: The results showed that family therapy could effectively improve character strengths and reduce self-injurious behaviors in adolescents aged 13-16. Keywords: Family therapy, Adolescent, Self-harm, Character strengths.